PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP MINAT BELAJAR DAN KETERAMPILAN PROSES SAINS SISWA PADA PEMBELAJARAN FISIKA DI SMAN BALUNG - Muhammad Khoirur Roziqin; Albertus Djoko Lesmono; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2018)
AbstractInterest in learning was one of the factors that affected student learningoutcomes. Physical learning in the form of products, processes and scientificattitude required skills that process on the scientific performance called the scienceprocess skills. Project-based learning presents learning in the form of scientificprocesses and attitudes that could foster students' learning motivation. This researchwas an experimental research. The purpose of this research was to examine theeffect of project based learning model on learning interest and students' scienceprocess skill in physics learning at SMAN Balung. Data of student's interest inphysics learning was obtained from questionnaire and data of science process skillobtained from post test and there were supporting data in the form ofdocumentation, interview, and observation. The result of the independent sample ttest on the interest of physics learning showed the interest of experimental classphysics learning better than the control class. While the results of mann-whitney teston the science process students 'skills showed the students' experimental classscience process skills better than the control class. Based on the analysis it could beconcluded that the project based learning model had a significant effected on thestudents' learning interest and science process skills on physics learning at SMANBalung.Keyword: interest, project based learning model, science process skill